Study of Digital Asset Inheritance: A Review of Contemporary Islamic Law in Indonesia - Dody Pratama; Saipudin (Istinbath : Jurnal Hukum, 2025)
This study aims to examine the legality of digital assets from the perspective of Islamic law and Indonesian positive law, as well as to analyze their status as inheritance objects under contemporary Islamic law. The development of digital technology has given rise to new forms of wealth, such as cryptocurrency, NFTs, electronic wallets, and digital accounts with economic value, which do not yet have a clear legal status as inheritance objects in the national legal system or contemporary fiqh. This study uses a qualitative method based on a literature review with a normative-dogmatic approach to analyze the Qur'an, Hadith, fiqh rules, contemporary literature, and Indonesian regulations related to digital assets and economic rights. The results of the study show three main findings: (1) normatively, digital assets meet the criteria of māl mutaqawwam based on QS. al-Nisā' [4]:7; 11–12, the principles of al-aṣl fī al-asyyā’ al-ibāḥah, al-‘ādah muḥakkamah, and analogy to ḥuqūq māliyah, making them valid objects of inheritance; (2) the mechanism of digital inheritance requires asset inventory, access assurance through wills/digital executors, distribution in accordance with sharia provisions, and privacy protection as an implementation of the principle of ḥifẓ al-‘irḍ; and (3) there is a need for legal harmonization through the establishment of national regulations, the formulation of comprehensive fatwas, and the improvement of digital literacy among the public. [Penelitian ini bertujuan untuk mengkaji legalitas aset digital dalam perspektif hukum Islam dan hukum positif Indonesia, serta menganalisis kedudukannya sebagai objek waris menurut hukum Islam kontemporer. Perkembangan teknologi digital melahirkan bentuk kekayaan baru seperti cryptocurrency, NFT, dompet elektronik, dan akun digital bernilai ekonomi yang belum memiliki kejelasan status hukum sebagai objek waris dalam sistem hukum nasional maupun fikih kontemporer. Penelitian ini menggunakan metode kualitatif berbasis studi kepustakaan dengan pendekatan normatif-dogmatis untuk menganalisis nash al-Qur’an, Hadis, kaidah fikih, literatur kontemporer, serta regulasi Indonesia terkait aset digital dan hak ekonomi. Hasil penelitian menunjukkan tiga temuan pokok: (1) secara normatif, aset digital memenuhi kriteria māl mutaqawwam berdasarkan QS. al-Nisā’ [4]:7; 11–12, kaidah al-aṣl fī al-asyyā’ al-ibāḥah, al-‘ādah muḥakkamah, dan analogi terhadap ḥuqūq māliyah, sehingga sah menjadi objek waris; (2) mekanisme waris digital mensyaratkan inventarisasi aset, penjaminan akses melalui wasiat/eksekutor digital, distribusi sesuai ketentuan syariah, serta perlindungan privasi sebagai implementasi prinsip ḥifẓ al-‘irḍ; dan (3) terdapat kebutuhan harmonisasi hukum melalui pembentukan regulasi nasional, penyusunan fatwa komprehensif, serta peningkatan literasi masyarakat digital].